2019
DOI: 10.1097/meg.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of urinary neutrophil gelatinase-associated lipocalin and serum cystatin C in a cohort of liver cirrhosis patients with renal dysfunction: a challenge in the diagnosis of hepatorenal syndrome

Abstract: Objectives This study aimed to assess urinary neutrophil gelatinase-associated lipocalin (uNGAL) and serum cystatin C (sCys C) in liver cirrhosis patients with renal dysfunction and to evaluate their role in the diagnosis of the hepatorenal syndrome (HRS). Patients and methods Forty-five liver cirrhosis patients were enrolled in the study and they were divided into three groups; the first group included 15 patients with normal renal function, the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…33 Both NGAL and CystC are early biomarkers of AKI and are currently widely used clinically. In this study, urine NGAL and serum CystC showed promising performance in predicting AKI and may become useful biomarkers for the occurrence of HRS in patients with liver cirrhosis and ascites, which was consistent with Gomaa et al 34 Remarkably, Previous studies have reported that urine biomarkers were related to the progression and mortality of AKI, especially urinary NGAL, which can discriminate ATN from HRS. 38,39 Another study also demonstrated that urinary NGAL, renal RI, and serum CystC may be useful in the differential diagnosis of AKI and the prognosis of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 91%
“…33 Both NGAL and CystC are early biomarkers of AKI and are currently widely used clinically. In this study, urine NGAL and serum CystC showed promising performance in predicting AKI and may become useful biomarkers for the occurrence of HRS in patients with liver cirrhosis and ascites, which was consistent with Gomaa et al 34 Remarkably, Previous studies have reported that urine biomarkers were related to the progression and mortality of AKI, especially urinary NGAL, which can discriminate ATN from HRS. 38,39 Another study also demonstrated that urinary NGAL, renal RI, and serum CystC may be useful in the differential diagnosis of AKI and the prognosis of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 91%
“…Serum cystatin C, which is released by all nucleated cells and eliminated by glomerular filtration, has been studied extensively for accurate estimation of glomerular filtration rate (GFR). 23 27 The combination of cystatin C and sCr was able to calculate GFR more accurately compared to sCr alone, especially when GFR is below 60 ml/min. 28 This should allow for a more accurate representation of a reduction of GFR.…”
Section: Diagnosis Of Hrs-akimentioning
confidence: 98%
“…The majority of the HRS-AKI episodes are precipitated by an acute event. It is important to identify all the precipitating events and treat them [23][24][25][26][27] The combination of cystatin C and sCr was able to calculate GFR more accurately compared to sCr alone, especially when GFR is below 60 ml/min. 28 This should allow for a more accurate representation of a reduction of GFR.…”
Section: Pathophysiology Of Aki In Cirrhosismentioning
confidence: 99%
“…Serum cystatin C may be a more accurate marker of kidney function in cirrhosis and can be utilized when readily available 11,12 .…”
Section: Interpretation and Applicability Of Ica Diagnostic Criteriamentioning
confidence: 99%